African American male pathways to college: a multi-institutional study of family involvement and influence - Johnson, Gralon Almont (Kansas State University, 2015)
Perceptions of family influence as a source of motivation to attend college were explored. More specifically, the purpose of this study was to investigate how, and in what ways, families shaped the pathway to higher education among 12 African American male collegians. Comparisons of these perceptions across family compositions and an extant model of family influence and college choice were also explored. The students in this study attended both public and private 4-year historically Black and predominantly White colleges situated throughout seven states in the Midwest and the South. A phenomenological qualitative research approach was employed to forward this study. Also, interpretive phenomenological analysis (IPA) techniques were applied to data gleaned from face-to-face interviews. Results of the study revealed two overarching themes of family influence and college choice for African American males: (1) deliberate family involvement and (2) contextual family influences. Eight subthemes illuminate the overarching theme deliberate family involvement: (1) emphasizing hard work, (2) aiding with pre-college paperwork, (3) offering messages about value of college, (4) supporting extra-curricular activities, (5) encouraging positive decision-making, (6) cultural indoctrination, (7) providing affirming words and praise, and (8) regular accessibility. Four subthemes buttress the overarching theme contextual family influence: (1) family educational choices, (2) family participation, (3) family representation and reactions, and (4) family stress. Implications for practice and recommendations for future research are also presented.
Keywords: African American families; African American males; College choice; Family decision making; African American Studies (0296); Higher Education (0745)